Spatial Diagnosis and Conceptualisation of Greening Plan of Seme-Podji, Benin (West Africa) - Osseni, Abdel Aziz; Gbesso, Gbodja Houéhanou François; Akabassi, Ghislain Comlan; Akakpo, Bokon A. (Journal of Environmental Geography, 2023)
Conservation and sustainable management of natural resources are increasingly recommended in decentralized territories. The most effective approach for this process is the participation of local communities because their knowledge is valuable in policy implementation. The study aims to propose a sustainable management model of a territory based on the needs of communities in order to conserve the natural resources in the Sèmè-Podji municipality in Benin, West Africa. Local knowledge and community’s needs have been used in association with GIS technics to make a diagnosis of the territory and propose a land use map for the municipality. The spatial diagnosis revealed an anthropization of the land cover, with a predominance of agro-systems, built up areas, croplands and fallow which represent 80.03% of the total area of the municipality. The marshlands which mostly serve as a refugium and support biodiversity represent 5.42%. The proposed plan showed that 84.79% (p ˂ 0.001) of socio-professional needs are explained. Therefore, the proposed actions were related to the restoration of ecological continuity, creation of new green recreational spaces, the protection of marshlands, the management of natural protected areas and the creation of fuel wood tree plantations. The current information can contribute to a sustainable and inclusive landscape planning for such municipalities, like our study site at Sèmè-Podji in Benin.